Game-Based Auxiliary Training System for improving visual perceptual dysfunction in children with developmental disabilities: A proposed design and evaluation. (September 2018) - Wuang, Yee-Pay; Chiu, Yu-Hsien; Chen, Yenming J.; Chen, Chiu-Ping; Wang, Chih-Chung; Huang, Chien-Ling; Wu, Tang-Meng; Ho, Wen-Hsien
Abstract: The main purpose of this study was to develop and evaluate a Game-Based Auxiliary Training System (GBATS) in special education for improving visual perceptual dysfunction in children with developmental disabilities. The GBATS application program was designed in the first stage of the study. Sixty participants with visual perceptual dysfunction were then randomly assigned to either an experimental group or a control group ( n = 30 each) to evaluate the effectiveness of the GBATS. The experimental group received the GBATS while the control group received the Conventional Visual Perceptual Training Program (CVPTP). Both the GBATS and CVPTP were administered in two 30-min sessions per week for 8 weeks. The post-intervention outcome measures were the Test of Visual Perceptual Skill, Third Edition, the Vineland Adaptive Behavior Scale, and the School Function Assessment. At post-intervention, the GBATS group significantly outperformed the CVPTP group in all three measures. Specifically, children in the GBATS group showed significantly larger improvements in demonstrated benefit in improving visual perceptual function. The GBATS group also showed significantly larger improvements in adaptive behaviors and school functions. The present study shows that the GBATS can be used as a training program adjuvant to other rehabilitative interventions that have proven effective for treating visual perceptual dysfunction in children. Highlights: A game-based system was developed for children with developmental disabilities. Experimental group outperformed control group in all measures at post-intervention. Experimental group showed in improving visual perceptual function. Experimental group showed improvements in adaptive behaviors and school functions.